Chemopreventive property of dietary ginger in rat urinary bladder chemical carcinogenesis - Ihlaseh, Shadia Muhammad; Oliveira, Maria Luiza Cotrim Sartor de [UNESP]; Teran, Elizabeth; Camargo, João Lauro Viana de [UNESP]; Barbisan, Luis Fernando [UNESP] (Springer, 2006)
The modifying potential of ginger on the development of preneoplasia and tumors in the male Wistar rat urinary bladder was investigated in a 36-week-long initiation-promotion assay for chemical carcinogenesis. Groups G1 to G3 were given 0.05% N-butyl-N-(4-hydroxybutyl)-nitrosamine (BBN) in drinking water for 5 weeks and a 3% uracil meal for the subsequent 3 weeks. Groups G4 and G5 were treated with 3% uracil only for the same period. After these steps, groups G2, and G3 and G4 were fed for 26 weeks a ginger extract mixed at 0.5 and 1.0% in a basal diet, respectively. Thirty six weeks after the beginning of the experiment all rats were killed. The multiplicity of urothelial lesions (hyperplasia and neoplasia) was significantly lower (P = 0.013) in group G3 than in groups G1 and G2. The results suggest that 1.0% ginger meal exerts a protective effect on the post-initiation stage of rat chemically-induced urothelial carcinogenesis.
Keywords: ginger; chemoprevention; rat urothelial carcinogenesis